Recovery of phosphate from aqueous solutions using calcined eggshell as an eco-friendly adsorbent. - Santos, Andreia F.; Arim, Aline L.; Lopes, Daniela V.; Gando-Ferreira, Licínio M.; Quina, Margarida J. (Journal of Environmental Management, 2019)
Abstract Phosphorus scarcity has become a significant issue in the European Union (EU) during 21st Century, due to its relevance as an irreplaceable macronutrient for life, and because of the total dependency of EU regarding imports. This work aims to evaluate the phosphorus recovery by adsorption in batch and fixed-bed column, using a thermally modified eggshell as an adsorbent. The screening phase revealed that calcined eggshell at 700 °C (CES700) is the most suitable material compared with the other thermally modified eggshells tested. Thus, CES700 was characterized regarding the specific surface area, pore volume, zero-point charge pH, total dissolved solids and organic matter. The influence of pH and adsorbent dosage was investigated in batch conditions. Langmuir-Freundlich model described the equilibrium data and the maximum adsorption capacity was about 39 mg P-PO 4 /g. The kinetics follows a pseudo-first order model, with constants between 0.063 and 0.224 min. Fixed-bed studies indicated that increasing fluid superficial velocity and feed concentration led to an early saturation of the adsorbent. Yoon-Nelson, Thomas and Bohard-Adams empirical models properly adjusted the breakthrough curves with R ≥ 0.98. Germination tests using CES700 loaded with phosphate revealed a germination index of 120 and 124% to 48 and 72 h, respectively. CES700 is statically better than the other tested materials, which opens the possibility of its use as fertilizer. This study showed that the developed material, CES700, can be applied in batch or fixed-bed processes to recover phosphate ions from liquid effluents, and the loaded adsorbent has potential to be further used as fertilizer. Highlights • Calcined eggshell at 700 °C (CES700) has good performance as adsorbent for phosphate. • The main crystalline phase of CES700 is calcite. • CES700 is chemically stable in batch and fixed-bed column operation. • Langmuir-Freundlich isotherm and the pseudo-first order model described the data. • CES700 loaded with phosphate may be valorized as fertilizer.